(Teil‑)Arthrodesen am Handgelenk: Indikationen und chirurgische Therapien = (Partial) fusion of the wrist : indications and surgical procedures - Unglaub, Frank; Langer, Martin Franz; Unglaub, Julia Marie; Sauerbier, Michael; Müller, Lars Peter; Krimmer, Hermann; Hahn, Peter; Spies, Christian (Der Unfallchirurg, 2017)
Carpal bone fusions for secondary reconstruction are still indispensable despite state of the art diagnostic tools and modern treatment techniques for wrist lesions. The former fusions stabilize the wrist and enable sufficient residual carpal mobility. Pain can be reduced significantly by arthrodesis of destroyed joints and the progress of osteoarthritis may be stopped or delayed. This review presents commonly used fusions with their inherent indications, contraindications and complications.